KEPEMIMPINAN INKLUSIF DI TENGAH ISUBREAKING THROUGH THEGLASS CEILINGSYNDROME: BEST PRACTICEPADA BIRO PERENCANAAN KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN REPUBLIK INDONESIA - Annisa Dewi Mantika Setiawan; Kusnar Budi; Fitria Ariyanti (Universitas Diponegoro, 2025)
In public sector, the establishment of bodies or institutions, policies, and programs promoting equal access for women and men in education, health, economics, and law amid the trend of breaking through the glass ceiling syndrome continues to be pursued. Recognizing this phenomenon, the Ministry of Environment and Forestry (KLHK) of the Republic of Indonesia is actively advancing the implementation of Gender Mainstreaming (GM) as part of gender equality efforts amidst the breaking through the glass ceiling syndrome within its environment. The Planning Bureau of KLHK plays a significant role in GM implementation. Therefore, assessing a leader's inclusive leadership model in addressing the breaking through the glass ceiling syndrome trend is imperative. This research measures the level of inclusive leadership of the Head of the Planning Bureau KLHK amid the breaking through the glass ceiling syndrome trend through a mixed-method data collection technique. This study also analyzes and elaborates on the best practices of the Head of the Planning Bureau at KLHK leadership in addressing the trend of breaking through the glass ceiling syndrome. Quantitative data collection in this study is conducted through surveys, while qualitative data collection utilizes in-depth interviews and literature reviews. The respondents in this study comprised 30 female employees of the Planning Bureau KLHK. The research findings indicate that the level of inclusive leadership of the Head of the Planning Bureau KLHK falls within the high category. This is supported by both dimensions of inclusive leadership proposed by Ashikali (2019), namely cognitive and affective, which also fall within the high category. Furthermore, there are seven essential best practices in the leadership of the Head of the Planning Bureau at KLHK, which can serve as valuable examples for other working groups and public institutions in Indonesia.